Окружение Сталина - Медведев Рой Александрович (Жизнь замечательных людей, 2010)
Экземпляры: (20220413) / Инвентарный номер: 36445 / Цена: 577.06 / Сис.шифр: 63.3(2) / Авт.знак: М 42 / ГРНТИ: 03 / ББК: 63.3(2)